PERTUMBUHAN DAN PRODUKSI TOMAT (Lycopersicum esculentum Mill.) AKIBAT PERLAKUAN PUPUK NPK DAN PUPUK ORGANIK CAIR SABUT KELAPA - Widiyanto, Arif; Budiyanto, Susilo; Lukiwati, Dwi Retno (JURNAL AGROPLASMA, 2022)
The aim of the study was to evaluate the effect of the combination of doses of NPK fertilizer and coconut organic liquid fertilizer on the growth and production of tomato plants. The field experiment was carried out on October 7–December 30, 2021 at the Greenhouse Block C, and Ecology and Plant Production Laboratory, Faculty of Animal and Agricultural Sciences, Diponegoro University, Semarang Central Java. The study used a 4 x 3 factorial experiment on the basis of a completely randomized design (CRD) with 3 replications, so there were 36 experimental units. The first factor is the dose of NPK fertilizer with 4 treatment levels, namely NPK 375 kg/ha equivalent to 60 kg N/ha (according to the recommended dose equivalent to 7.5 g/plant = N1), NPK 281.25 kg/ha (75% recommended dose equivalent to 5.63 g/plant = N2), NPK 187.5 kg/ha (50% recommended dose equivalent to 3.75 g/plant = N3), and NPK 93.75 kg/ha (25% dose recommendation equivalent to 1.88 g/plant = N4). The second factor was the dose of coconut coir POC treatment with 3 levels, namely a dose of 300 ml of coconut fiber POC (K1), 500 ml of coconut fiber POC (K2) and 700 ml of coconut fiber POC (K3). Plant height, number of leaves, number of branches, stem diameter, flowering age, number of bunches per plant, number of fruits per bunch, number of fruits per plant, fruit diameter, fruit weight harvested, fruit weight per plant, and fruit quality were observed. The dataset obtained was analyzed for variance and further tested with Duncan's multiple distance test at the 5% level. The results showed that the dose of NPK fertilizer increased the number of branches, the number of bunches per plant, the number of fruits per bunch and the number of fruits per plant. Keywords: Coconut Organic Liquid Fertilizer, NPK, Tomat.Penelitian bertujuan untuk mengevaluasi pengaruh kombinasi antara dosis pupuk NPK dan POC sabut kelapa terhadap pertumbuhan dan produksi tanaman tomat. Penelitian telah dilaksanakan pada tanggal 7 Oktober – 30 Desember 2021 di Greenhouse Blok C, dan analisis laboratorium dilakukan di Laboratorium Fisiologi dan Pemuliaan Tanaman, Fakultas Peternakan dan Pertanian, Universitas Diponegoro, Semarang, Jawa Tengah. Penelitian menggunakan percobaan faktorial 4 x 3 dengan dasar rancangan acak lengkap (RAL) sebanyak 3 kali ulangan, sehingga terdapat 36 satuan unit percobaan. Faktor pertama adalah dosis pupuk NPK dengan 4 taraf perlakuan, yaitu NPK 375 kg/ha setara dengan 60 kg N/ha (sesuai dosis rekomendasi setara dengan 7,5 g/tanaman = N1), NPK 281,25 kg/ha (75% dosis rekomendasi setara dengan 5,63 g/tanaman = N2), NPK 187,5 kg/ha (50% dosis rekomendasi setara dengan 3,75 g/tanaman = N3), dan NPK 93,75 kg/ha (25% dosis rekomendasi setara dengan 1,88 g/tanaman = N4).  Faktor kedua adalah perlakuan dosis POC sabut kelapa dengan 3 taraf yaitu dosis 300 ml POC sabut kelapa  (K1), 500 ml POC sabut kelapa (K2) dan 700 ml POC sabut kelapa (K3). Parameter yang diamati adalah tinggi tanaman, jumlah daun, jumlah cabang, diameter batang, umur berbunga, jumlah tandan per tanaman, jumlah buah per tandan, jumlah buah per tanaman, diameter buah, berat buah panen, berat buah per tanaman dan kualitas buah. Data yang diperoleh dianalisis ragam dan uji lanjut dengan uji jarak berganda Duncan pada taraf 5%. Hasil penelitian menunjukkan bahwa Perlakuan dosis pupuk NPK meningkatkan jumlah cabang, jumlah tandan per tanaman, jumlah buah per tandan dan jumlah buah per tanaman. Kata kunci: POC Sabut Kelapa, NPK, Tomat.